Gerakan Populis sebagai Tren Global: Dari Amerika Latin sampai Occupy Movement - Darmawan, Arif (Insignia: Journal of International Relations, 2017)
AbstractThe gap in Latin American countries is a fertile ground for the emergence of a populist movement, so that populism is not considered as a deviation, but become a rational alternative to address the problems rooted in the failure of the nation-building process. The existence of populism in Latin America indirectly also has an influence on the movement rooted in populism in the global sphere. This paper will analyze the close connection between the recent wave of populism in the international world by looking at the historical roots of how populism developed in Latin America and its effect on the “Occupy Movement” movement phenomenon in order to know how the pattern of populist movements in the global realm. This article will begin by understanding the clear definition of what is populism, then the roots of populist history in Latin America, and how it relates to the emergence of the Occupy Movement as a new form of populist movement that is becoming a global tren.Keywords: populism, Latin America, Occupy MovementAbstrakKesenjangan yang terjadi di negara-negara Amerika Latin memang menjadi lahan subur munculnya gerakan populis, sehingga populisme tidak dianggap sebagai sebuah penyimpangan, tetapi menjadi satu bentuk alternatif rasional untuk mengatasi permasalahan yang berakar pada kegagalan proses nation-building. Keberadaan populisme di Amerika Latin ini secara tidak langsung juga mempunyai pengaruh terhadap gerakan yang berakar pada populisme di ranah global. Makalah ini akan menganalisis keterkaitan yang erat antara gelombang populisme yang akhir-akhir ini terjadi di dunia internasional dengan melihat akar sejarah bagaimana populisme berkembang di Amerika Latin serta pengaruhnya terhadap fenomena pergerakan Occupy Movement dengan tujuan untuk mengetahui bagaimana pola gerakan populisme di ranah global. Artikel ini akan mengawali dengan memahami definisi yang jelas mengenai apa itu populisme, kemudian akar sejarah populisme di Amerika Latin, dan bagaimana keterkaitannya dengan kemunculan Occupy Movement sebagai bentuk gerakan populis baru yang menjadi tren global.Kata kunci: populisme; Amerika Latin; Occupy Movement